HOW HAS THE USE OF ARTIFICIAL INTELLIGENCE CONTRIBUTED TO THE PEANUT CULTURE? - Dalpian, Diego Cezar; Mendes, Oswaldo Lazaro (Revista Interface Tecnológica, 2022)
Peanut is an important food that contributes to world food security. This exploratory bibliometric study used the SCOPUS database as a query and sought to show which studies, with the use of artificial intelligence, were carried out in the last ten years in the peanut crop. The result showed that there are few studies on this topic and that the application of artificial intelligence to data from management and decision-making sensors can contribute to producers and managers in the assertiveness of their administration, and can therefore add value to products, increase the profitability, productivity, and sustainability of agricultural businesses by understanding the data set.
Keywords: Machine learning; E-agriculture; Remote sensing; Strategic management